SLFN11: a pan-cancer biomarker for DNA-targeted drugs sensitivity and therapeutic strategy guidance - Zhou, Kunzhong; Li, Yuewen; Wang, Weifang; Chen, Yilin; Qian, Bingyan; Liang, Yiteng; Li, Hongmei; Xu, Ruiting; Zhuang, Li (Frontiers in Oncology, 2025)
Therapeutic responses to identical chemotherapy regimens often vary significantly among patients with the same type of cancer, underscoring the need for additional biomarkers to identify individuals most likely to benefit from specific treatments. The expression of SLFN11 (Schlafen11) has been identified as a potential biomarker for predicting patient responses to DNA-damaging agents and PARP inhibitors, as it irreversibly blocks DNA replication under replication stress, thereby increasing the sensitivity of cancer cells to various DNA-damaging agents and PARP inhibitors. Preclinical and clinical trial data suggest that SLFN11 can predict therapeutic responses to multiple DNA- targeted drugs, including platinum-based agents, topoisomerase I/II inhibitors, DNA synthesis inhibitors, and PARP inhibitors. Leveraging the expression status of SLFN11 or modulating its expression offers exciting possibilities for clinical applications. In this review, we summarize the structure and function of SLFN11, as well as its progress as a biomarker across various cancer types. We also review the regulation of SLFN11 expression, its dynamic expression patterns, and potential strategies for combination therapies to enhance efficacy based on SLFN11 status. Furthermore, we discuss the potential of SLFN11 expression status in overcoming resistance to DNA-damaging drugs, optimizing treatment strategies, and advancing precision cancer therapy.